2016
DOI: 10.48550/arxiv.1607.01296
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conditionally generating a mesoscopic superposition of N00N states

Falk Töppel,
Maria V. Chekhova,
Gerd Leuchs

Abstract: We study the generation of superpositions of N00N states by overlapping few-photon-subtracted squeezed vacuum states and coherent states on a 50/50 beam splitter. Assuming parameters that are feasible with current technology results in output states with mean photon numbers of several tens. We show that the generated quantum states violate local realism even in the presence of considerable loss. The occurrence of strong quantum correlations for mesoscopic quantum states of light is particularly beneficial for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…It is shown that the minimal value of J 3 merges for both states for low amplitudes, and deviates for larger average photon numbers, starting at n ≈ 1. We note that a similar analysis was recently done for CS mixed with photon subtracted SV [33].…”
Section: Nonlocality and The Janssens Inequalitysupporting
confidence: 56%
“…It is shown that the minimal value of J 3 merges for both states for low amplitudes, and deviates for larger average photon numbers, starting at n ≈ 1. We note that a similar analysis was recently done for CS mixed with photon subtracted SV [33].…”
Section: Nonlocality and The Janssens Inequalitysupporting
confidence: 56%
“…In addition, studying the distribution of the QFI and CFI in the N-photon components also helps to understand the phase estimation precision in recent post-selection experiments. When the MZI is fed by the coherent ⊗ squeezed vacuum, the state after the first beam splitter of the MZI contains a small fraction of the path-entangled NOON state [21,22], which is a well-known N-photon non-classical state that allows the phase estimation precision to achieve the Heisenberg limit [23][24][25][26][27][28][29]. In the limit |α| 2 , |ξ| ≪ 1, Afek et al [22] have demonstrated N-fold oscillations of the coincidence rates for N up to 5, manifesting the appearance of N-photon NOON states.…”
Section: Introductionmentioning
confidence: 99%